Effect of Curcuma longa (Turmeric) on serum creatine kinase-MB and troponin I in isoproterenol induced myocardial infarction in wistar albino rats - Nahar, Sharmin; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2018)
Background: The prevalence of myocardial infarction (MI) is increasing day by day in Bangladesh due to socioeconomic transition. Spices and herbs are important source of remedy for various diseases in human. Curcuma longa suggested to be used as an indigenous medicine for the prevention and treatment of cardiovascular disease. Objective: To observe the effect of Curcuma longa in isoproterenol induced myocardial infarction in Wistar albino rats. Methods: This experimental study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka during 2015. Twenty one Wistar albino male rats, weighing 100 to 150 g (initial body weight); aged 85 to 100 days were selected for the study. After acclimatization for 14 days, the rats were divided into BC (Baseline control group), ISP-TC (Isoproterenol treated control group) and CLP-ISPT (Curcuma longa pretreated and isoproterenol treated group). Each group consisted of 7 rats. After experiment, on the 10th day, final body weight was taken, rats were sacrificed and blood samples were collected from the heart. The heart was removed and weighed. Serum creatine kinase-MB (CK-MB) level was estimated by ELISA method and Troponin I (cTnI) level by AxSYM method. The statistical analysis was done by one way ANOVA and Bonferroni test as applicable. Results: In this study, the mean percent (%) change of body weight (p<0.01), mean serum CK-MB (p<0.001) and cTnI (p<0.001) levels were significantly higher but mean heart weight was non significantly higher in ISP-TC in comparison to those of BC. Again, the mean percent (%) change of body weight (p<0.01), mean heart weight (p<0.01), mean serum CK-MB (p<0.01) and cTnI (p<0.001) levels were significantly lower in CLP-ISPT than those of ISP-TC group. Conclusion: From the results, it can be concluded that Curcuma longa may have cardioprotective effect. J Bangladesh Soc Physiol. 2018, December; 13(2): 47-53